Revisiting repatriation concerns: organizational support versus career and contextual influences - Lazarova, Mila B; Cerdin, Jean-Luc (Journal of International Business Studies, 2007)
This paper reviews and integrates two perspectives on repatriate retention: a traditional one, which suggests that the main determinant of repatriate retention is the availability of repatriation support programs; and an emerging one, which focuses on individual career activism in a changing employment context. Results of a study of 133 expatriates from 14 MNCs indicate that both views contribute to our understanding of repatriate retention. Building on the results of our study, we put forward a framework to guide future research.